Purple urine bag syndrome: an alarming and rare phenomenon of urine infection - Rawal, Gautam; Garg, Nitin; Yadav, Sankalp; Rasool Wani, Umar; Shokeen, Priyanka (International Journal of Medical Research and Review, 2015)
Purple urine bag syndrome (PUBS) is a rare but striking and an alarming medical phenomenon observed in patients having indwelling urinary catheters with co-existing urinary tract infections. It commonly occurs in bedridden elderly with constipation and long standing indwelling urinary catheters, and denotes bacterial urinary tract infection. The authors report a case of 77 year-old Indian male with purple coloration of his urinary drainage bag in the context of a urinary tract infection caused by Pseudomonas aeruginosa.